THE LIVED EXPERIENCE OF B.ED. STUDENT TEACHERS DURING TEACHING PRACTICE: THE TRAJECTORY TO BECOMING PROFESSIONALS - Wendy Setlalentoa; Mahlape Victoria Mokone (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This paper explores the lived experiences of Bachelor of Education (B.Ed.) student teachers during their teaching practice, a critical component of teacher training. Despite its importance, there is limited understanding of the student-teacher’s experiences within the teaching and learning environment. The study addresses the following central question: What are the lived experiences of student teachers during teaching practice? Using qualitative research methods, this paper investigates the day-to-day realities of student teachers, considering their challenges, successes, and overall professional development during this formative period. The study is grounded in Social Learning Theory, as proposed by Albert Bandura, which underscores the significance of observational learning, imitation, and modelling in the development of behaviour and professional identity. Bandura’s framework highlights the interaction between environmental and cognitive factors, which shape learning and behaviour. This theoretical approach is relevant to understanding how student teachers absorb knowledge, behaviours, and attitudes from their mentors and the teaching environment, influencing their trajectory toward becoming professional educators. The study employed a purposive sample of 20 student teachers from Central University of Technology, with a balance of 10 third year and 10 fourth-year students. Data were collected through focus group interviews to capture rich qualitative insights into their teaching practice experiences. Thematic analysis was used to identify recurring patterns and themes in the data. Findings reveal that many student teachers felt inadequately prepared for the challenges of the classroom. In several cases, a lack of support from mentor teachers and other institutional role players during teaching practice further exacerbated their difficulties. These gaps in preparation and mentorship contributed to feelings of uncertainty and stress, while simultaneously underscoring the critical need for robust support systems to facilitate the professional growth of student teachers. The paper concludes by discussing the implications of these findings for teacher education programs, suggesting that improved mentoring structures and better alignment between theoretical training and practical application are essential for preparing student teachers to transition effectively into professional roles.